Effect Of Different Webbing To Catch Fish (Rasbora Sp) With Gill Nets Fishing Gear - Joko Frima Manihuruk; Nofrizal '; Isnaniah ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on May 2015 in Kampar river waters, BuluhCina village, Siak Hulu District, Kampar Regency, Riau Province. The purpose ofthis study was to determine the webbing is effective for catching fish (Rasbora sp)using gill nets. The data collected in this study include the type of fish, the amountof fish caught in weight (grams), individuals (tail) and fish caught are snagged,gilled, wedged and entangled hereinafter abbreviated as SGWE. Data wereanalyzed, namely the amount of catches and how to Rasbora sp caught in gill netsby using completely randomized design (CRD), with three treatments and 10repetitions. Webbing different obtainable catches Rasbora sp the most is the whitewebbing that as many as 234 fish with a weight of 6,027 grams, and the least isthe blue webbing as much as 78 tails, weighing 2,078 grams. The results ofANOVA for the number and weight of fish catches Rasbora sp obtained Fhit>Ftab the meaning of there is a significant effect between treatments wereattempted. The white color is more effective fishing gear to catch fish (Rasborasp) using gill nets.Keywords: webbing, gill nets.